A modified Euler–Maruyama method for Riemann–Liouville stochastic fractional integro-differential equations. Issue 2 (22nd January 2023) - Zheng, Yu; Qian, Siying; Arshad, Sadia; Huang, Jianfei
Abstract : In this paper, we propose a modified Euler–Maruyama (EM) method for Riemann–Liouville stochastic fractional integro-differential equations with weakly singular kernels, and then analyse the strong convergence of the proposed EM method. Specifically, we transform the considered stochastic fractional integro-differential equation into its equivalent form of stochastic Volterra integral equations and derive the corresponding modified EM method. Then, the strong convergence 1 − α order of the proposed method is established, where α is the order of Riemann–Liouville fractional derivative with 0 < α < 1 . Finally, numerical experiments are demonstrated to support our theoretical results.